Circadian rhythms in human muscular efficieny: Continous physical exercise versus continous rest: A crossover study - Callard, D.; Davenne, D.; Gauthier, A.; Lagarde, D.; Van Hoecke, J. (Chronobiology International, 2000)
This study deals with the influence of time of day on neuromuscular efficiency in competitive cyclists during continuous exercise versus continuous rest. Knee extension torque was measured in ultradistance cyclists over a 24h period (13:00 to 13:00 the next day) in the laboratory. The subjects were requested to maintain a constant speed (set at 70% of their maximal aerobic speed obtained during a preliminary test) on their own bicycles, which were equipped with cyclosimulators. Every 4h, torque developed and myoelectric activity were estimated during maximal isometric voluntary contractions of knee extensors using an isokinetic dynamometer. Mesenteric temperature was monitored by telemetry. The same measures were also recorded while the subjects were resting awake until 13:00 the next day. During activity, torque changed within the 24h period (p < .005), with an acrophase at 19:10 and an amplitude of 7.8% around the mean of 70.7%. At rest, a circadian rhythm was observed in knee extensor torque (p < .05), with an acrophase at 19:30 and an amplitude of 6% around the mean of 92.3%. Despite the standardized conditions, the results showed that isometric maximal strength varied with time of day during both a submaximal exercise and at rest without prior exercise. The sine waves representing these two rhythms were correlated significantly. Although at rest the diurnal rhythm followed muscular activity (i.e., neurophysiological factors), during exercise, this rhythm was thought to stem more from fluctuations in the contractile state of muscle. Source: Chronobiol Int 2000 Sep;17(5):693-704